THE IMPORTANCE OF THE STEAM EDUCATIONAL APPROACH IN TECHNOLOGY - Majidova , Khurriyat; Burxonov , Rasul (MMIT Proceedings, 2023)
In our country, in the following five years, special attention was paid to the educational system, as in all areas. In New Uzbekistan-during a new worldview period, a new revision of the law “On education” was adopted and the educational system was updated. The modern educational process is studied in the educational technologies of developed foreign countries and pays special attention to the further development of the educational system of our country. One such technology is STEAM and SMART educational technology. The continuous development of these technologies is changing the way students learn, research and interact with them in the day. This article examines the importance of STEAM education, which is currently considered important in the world education system, using the example of Technology Science. Reflections on the progress trends in technology science and the compatibility of STEAM education areas, the effectiveness of this approach in practical teaching processes are presented